1927
DOI: 10.1007/bf01395494
|View full text |Cite
|
Sign up to set email alerts
|

Das erweiterte Gesetz von Matthiessen

Abstract: Das bekann~e Gesetz tiber das elektrische Verhalten yon Zweistoffsvstemen hat l~[atthiesse~ urspriinglich formulier~ wie folgtl):,,Die gefundene prozen~ische Abnahme in der Leitungsf~higkeit einer Legierung zwischen 0 und 100 ~ C verhiilt sich zu der herechneten wie die beobachtete Lei~ungsf~ihigkeit der I,egierung bel 100~ zu der bereehneten bei 100 ~ Unfer .,berechneter Leitungsfiihigkeif" wird hierbei die ..aus den Votumina entsprechenden :Paralle]drithten der komponierenden Metal]e" sich ergebende Leitf~hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1927
1927
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…3 indicates increasing film purity and decreasing structural defects with increasing deposition temperature. At 600~ the film resistivity and its temperature coefficient approach the values of the bulk metal and are similar to those of drawn pure molybdenum wire (10). Mattiessen's rule holds with fair approximation as shown in column V of Table I.…”
Section: Film Propertiessupporting
confidence: 52%
“…3 indicates increasing film purity and decreasing structural defects with increasing deposition temperature. At 600~ the film resistivity and its temperature coefficient approach the values of the bulk metal and are similar to those of drawn pure molybdenum wire (10). Mattiessen's rule holds with fair approximation as shown in column V of Table I.…”
Section: Film Propertiessupporting
confidence: 52%
“…In this context a paper by Geiss and v. Liempt (Philips, Eindhoven) should be mentioned, too. [11] In 1934 van Arkel summarized the state of knowledge in a review article "Die Herstellung hochschmelzender Metalle durch Dissoziation ihrer Verbindungen" (Formation of refractory metals by dissociation of their compounds). [12] It is noteworthy that the works of Mond, Langer, and Quincke, of Langmuir as well as those of van Arkel and De Boer are strongly related to, if not driven by technical applications.…”
Section: From the Roots To The First Model Conceptsmentioning
confidence: 99%
“…During recent work in this laboratory (Broom 1952) on the resistivity of cold-drawn wires, some results were found which suggested deviations from the rule. The most recent systematic work on the validity of the rule for a metal in various states of deformation is that by Geiss :and van Liempt (1925, 1927 who found that, for tungsten, molybdenum, platinum, and nickel, deformation produced variations in the product of up to 2 per cent. They give no indication of their experimental error but conclude that the rule is true.…”
Section: Introductionmentioning
confidence: 99%